Islamic Education Management in Promoting Multiculturalism, Democracy and Harmony - Muthoifin, Muthoifin; Elbanna, Mariam; Barry, Aboubacar; Afiyah, Ishmah; Nirwana, Andri; Bernardlauwers, Bernardlauwers; Islam, Rezaul (Journal of Management World, 2025)
Islamic education plays a vital role in promoting multiculturalism and fostering democratic harmony by instilling values of tolerance, respect, and coexistence. This study aims to explore how the principles of Islamic education can contribute to building a society that values diversity and upholds democratic ideals. To achieve this, a qualitative approach is employed, utilizing both primary and secondary sources such as religious texts, educational curricula, and scholarly articles. The study examines the teachings of Islam on social justice, equality, and respect for different cultures and religions, and how these values can shape educational practices and support societal integration. The findings indicate that when Islamic education is taught inclusively, it has the potential to bridge cultural divides and foster cooperation among diverse communities. In conclusion, the study emphasizes the significance of incorporating Islamic educational values into the development of a more harmonious and democratic society. The Prisma framework was used to ensure a systematic review of relevant literature and the integration of diverse sources. Key research questions explored in this study include: How can Islamic education promote multicultural understanding? What principles within Islamic teachings support democratic values and diversity? How can Islamic education be implemented to enhance social cohesion in multicultural societies?